Meconium Peritonitis and Periorchitis: Report of a Prenatal Case - Cem Yaşar Sanhal; İnanç Mendilcioğlu; Adnan Aslan; Murat Özekinci; Mehmet Şimşek (Gynecology Obstetrics & Reproductive Medicine)
Meconium peritonitis refers to rupture of the bowel prior to birth, resulting in fetal meconium escaping into peritoneum leading to inflammation (peritonitis). Meconium periorchitis is an extension of meconium peritonitis into the scrotum via a patent processus vaginalis. The most common causes of meconium peritonitis are ischemic lesions of the small bowel associated with mechanical obstruction (atresia, volvulus, intussusception, congenital bands, Meckel diverticulum and internal hernia). These likely account for 50% of the cases of meconium peritonitis. Meconium peritonitis may also be caused by viral infections (cytomegalovirus or parvovirus B19) and cystic fibrosis. Here, we report of a patient with fetal meconium peritonitis - periorchitis and perinatal management.